2017
DOI: 10.15252/embr.201643581
|View full text |Cite|
|
Sign up to set email alerts
|

Circ HIPK 3 sponges miR‐558 to suppress heparanase expression in bladder cancer cells

Abstract: Increasing evidences suggest that circular RNAs (circRNAs) exert crucial functions in regulating gene expression. In this study, we perform RNA-seq and identify 6,154 distinct circRNAs from human bladder cancer and normal bladder tissues. We find that hundreds of circRNAs are significantly dysregulated in human bladder cancer tissues. We further show that circHIPK3, also named bladder cancer-related circular RNA-2 (BCRC-2), is significantly down-regulated in bladder cancer tissues and cell lines, and negativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
452
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 475 publications
(475 citation statements)
references
References 46 publications
13
452
1
1
Order By: Relevance
“…CircHIPK2 increased SIGMAR1 expression by suppressing miR-124-2HG activity [22]. In bladder cancer, circHIPK3 affected the expression of heparanase by competitively binding to miR-558 [23]; circRNA MYLK and lncRNA H19 increase the expression of DNMT3, VEGFA, and ITGB1 by suppressing miR-29a-3P activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…CircHIPK2 increased SIGMAR1 expression by suppressing miR-124-2HG activity [22]. In bladder cancer, circHIPK3 affected the expression of heparanase by competitively binding to miR-558 [23]; circRNA MYLK and lncRNA H19 increase the expression of DNMT3, VEGFA, and ITGB1 by suppressing miR-29a-3P activity [24].…”
Section: Discussionmentioning
confidence: 99%
“…Li et al . found that circHIPK3 exerted inhibitory influence on human invasive bladder cancer T24T and UMUC3 cells by regulating miR‐558 . Additionally, previous researches revealed that circRNA‐MYLK functioned as an endogenous sponge for miR‐29a in bladder cancer.…”
Section: Discussionmentioning
confidence: 95%
“…The pull‐down assay with biotinylated RNA was performed as described . In brief, for circRUNX2 pulled down miRNAs, the biotinylated‐circRUNX2 probe was incubated with C‐1 magnetic beads (Life Technologies, Carlsbad, CA, USA) to generate probe‐coated beads, then incubated with sonicated HBMSCs at 4°C overnight, followed by eluted and qRT‐PCR.…”
Section: Methodsmentioning
confidence: 99%